(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2020)
Facing the number of cases of coronavirus infection (COVID-19), the World Health Organization (WHO) has declared that the disease, present in several countries and continents, is a pandemic of global alert and mobilization1. In Brazil, the pandemic arrived at the end of February 2020 and has been causing alarm due to the increase in the number of contaminated people related to the high capacity of transmission of the disease. In affected patients, the virus can cause from simple symptoms, which can be treated at home, to hospital admissions, assistance in intensive care units and can even lead to death2. In the midst of this pandemic, the professionals who assist patients with suspected or confirmed COVID-19 infection constitute a population at high risk of contagion. In this way, preventive measures such as adequate hand hygiene and the use of personal protective equipment(PPE) have been reinforced.